2010
DOI: 10.1128/jcm.00277-10
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Analysis of Colonizing Group B Streptococcus , Serotype IV, an Emerging Pathogen in the United States

Abstract: Colonizing group B Streptococcus (GBS) capsular polysaccharide (CPS) type IV isolates were recovered from vaginal and rectal samples obtained from 97 (8.4%) nonpregnant women of 1,160 women enrolled in a U.S. multicenter GBS vaccine study from 2004 to 2008. Since this rate was much higher than the rate of prevalence of 0.4 to 0.6% that we found in previous studies, the isolates were analyzed by using surface protein profile identification, pulsed-field gel electrophoresis (PFGE), and multilocus sequence typing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
52
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 46 publications
6
52
1
Order By: Relevance
“…The same scenario was observed among neonatal (2/64 cases; 3%) for the years 2000 to 2004 [12] and non-pregnant adult infections (2/225 cases; 1%) from 2001 to 2008 [14]. After 2010, reports from Brazil Ireland and the US [15][16][17][18] revealed an increased prevalence of serotype IV in colonisation and infection, suggesting the possibility that this serotype could be emerging as an important pathogen, as happened with serotype V during the 1990s [19].…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…The same scenario was observed among neonatal (2/64 cases; 3%) for the years 2000 to 2004 [12] and non-pregnant adult infections (2/225 cases; 1%) from 2001 to 2008 [14]. After 2010, reports from Brazil Ireland and the US [15][16][17][18] revealed an increased prevalence of serotype IV in colonisation and infection, suggesting the possibility that this serotype could be emerging as an important pathogen, as happened with serotype V during the 1990s [19].…”
Section: Introductionsupporting
confidence: 62%
“…This situation has changed in the last decade, when some countries, including the US, saw the emergence of serotype IV among colonising and invasive GBS isolates [15,16]. This scenario may become risky if the emergence of serotype IV combines with antibiotic resistance, which was the case in our study where co-resistance to second-line macrolide antibiotics was observed in recent years (2010-2012).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…To our knowledge, this proportion is the highest ever reported for serotype IV GBS adult invasive disease. While we did not characterize the GBS serotype distribution among colonized pregnant women (these studies are under way in our laboratories), others have observed increasing numbers of serotype IV strains among colonizing isolates (17,18,(38)(39)(40). Studies aimed at developing a capsular polysaccharide antigen-based GBS vaccine are ongoing worldwide, with several formulations that do not include serotype IV already under clinical trials (41).…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, longitudinal surveillance suggests that the proportion of serotype IV GBS isolates from nonpregnant adults increased from 0.2% in 1998 to 1999 to 5.7% in 2005 to 2006 (2). In 2010, serotype IV strains were shown to be responsible for 16% of early onset neonatal infections in the state of Minnesota (17,18). Consistent with this emergence, when we characterized a collection of 600 invasive strains from the province of Ontario, Canada, we found that serotype IV isolates were responsible for 6.2% of cases of GBS invasive disease (19).…”
mentioning
confidence: 99%